The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1467-6281.2009.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Abuse of Accounting in the Public Sector Financial Management Reform Program in Australia

Abstract: Accrual accounting has been central to financial management reforms designed to promote greater efficiency, effectiveness and accountability in the Australian public sector. This is the setting for the article; however, the issues covered apply to all nations that have reformed their public sectors over recent years. The results of the reforms have been mixed. While accrual accounting has had some beneficial results for the above purposes, the benefits have been offset by aspects of accounting misuse resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 38 publications
0
96
0
7
Order By: Relevance
“…Many public accounting scholars highlighted the fundamental difficulties generated by the adoption of accrual accounting (Adam, Mussari, & Jones, 2011;Barton, 2009;Biondi, 2012;Guthrie, 1998;Lapsley et al, 2009;Pina, Torres, & Yetano, 2009) as well as the practical difficulties of public administrations to effectively implement and/or utilize accrual accounting information in decisionmaking processes (Torres, Matsuo, & Pina, 2009). There had only been limited evidence available on the effectiveness of these systems so far.…”
Section: Epsas Ipsas and Accrual Accountingmentioning
confidence: 99%
“…Many public accounting scholars highlighted the fundamental difficulties generated by the adoption of accrual accounting (Adam, Mussari, & Jones, 2011;Barton, 2009;Biondi, 2012;Guthrie, 1998;Lapsley et al, 2009;Pina, Torres, & Yetano, 2009) as well as the practical difficulties of public administrations to effectively implement and/or utilize accrual accounting information in decisionmaking processes (Torres, Matsuo, & Pina, 2009). There had only been limited evidence available on the effectiveness of these systems so far.…”
Section: Epsas Ipsas and Accrual Accountingmentioning
confidence: 99%
“…Furthermore, several studies, starting with the one conducted by Brignall and Modell (2000), have assumed that accounting reforms may have been implemented by public managers primarily in order to seek legitimacy rather than maximize efficiency. Without adequate preparation of the path towards change, this approach has led to an underestimation of the difficulties related to its implementation (Barton, 2009;Christiaens and Rommel, 2008;Hepworth, 2003;Lüder and Jones, 2003), which involves an impact on people (cultural change), processes (innovation and integration), institutions (organizational change), and so on.…”
Section: Theoretical Background and The Development Of The Hypothesismentioning
confidence: 99%
“…Besides, they also suggested that budgeting is a means of coordinating governmental activities that imply financial consequences. However, if this control activity is acknowledged as important in a profit oriented business entity, it is also recognized as essential in governmental units (Barton, 2009). This is due to the fact that in public sector; budget embraces authorized expenditures and estimated revenues.…”
Section: Budgeting Systemsmentioning
confidence: 99%
“…Wildavsky (1984) highlighted the central role of budgeting systems in the management of public sector by suggesting that budgeting is the lifeblood of the government and the financial reflection of what the government does or intends to do. Therefore, regardless of the technique to be used, a budget should express what the government activities ought to be during a particular period of time in the light of limited resources (Ball, Dale, Eggers, & Sacco, 2000;Barton, 2009). In addition, Doost (1984) and Bargues (1992) emphasized the significant of budgeting system by explaining that budget is a tool for planning and controlling expenses, achievements and programs in government services.…”
Section: Budgeting Systemsmentioning
confidence: 99%